Preliminary Evidence on Impacts of Active Labor Programs in Hungary and Poland - Christopher J. O'Leary (W.E. Upjohn Institute for Employment Research, 1997)
To ease the hardship associated with worker dislocation and to maintain social stability during the transition to markets, the governments of Hungary and Poland provide labor force members with unemployment compensation and a variety of active labor programs (ALPs). Follow-up surveys of participants in retraining, public works, wage subsidies, self-employment, and comparison groups were done in Hungary and Poland in early 1997. Preliminary analysis suggests positive net impacts for most ALPs and additive benefits from the use of the employment service in both countries. Strong evidence of nonrandom assignment to programs means that great care should be used in interpreting the preliminary results and that further examination of the findings is necessary. Adjusted impact estimates for Hungary are provided, but supplementary data is needed from Poland to assess how representative the comparison groups are of the general population of registered unemployed workers.
Keywords: J0; J6; 330; unemployment; labor; market; programs; self-employment; Hungary; Poland; O'Leary